Understanding Water Storage Practices of Urban Residents of an Endemic Dengue Area in Colombia: Perceptions, Rationale and Socio-Demographic Characteristics - García-Betancourt, Tatiana (PLoS One, 2015)
INTRODUCTION: The main preventive measure against dengue virus transmission is often based on actions to control Ae. Aegypti reproduction by targeting water containers of clean and stagnant water. Household water storage has received special attention in prevention strategies but the evidence about the rationale of this human practice is limited. The objective was to identify and describe water storage practices among residents of an urban area in Colombia (Girardot) and its association with reported perceptions, rationales and socio-demographic characteristics with a mixed methods approach. METHODS: Knowledge, attitudes and practices and entomological surveys from 1,721 households and 26 semi-structured interviews were conducted among residents of Girardot and technicians of the local vector borne disease program. A multivariate analysis was performed to identify associations between a water storage practice and socio-demographic characteristics, and knowledge, attitudes and practices about dengue and immature forms of the vector, which were then triangulated with qualitative information. RESULTS: Water storage is a cultural practice in Girardot. There are two main reasons for storage: The scarcity concern based on a long history of shortages of water in the region and the perception of high prices in water rates, contrary to what was reported by the local water company. The practice of water storage was associated with being a housewife (Inverse OR: 2.6, 95% CI 1.5 -4.3). The use of stored water depends on the type of container used, while water stored in alberca (Intra household cement basins) is mainly used for domestic cleaning chores, water in plastic containers is used for cooking. CONCLUSIONS: It is essential to understand social practices that can increase or reduce the number of breeding sites of Ae. Aegypti. Identification of individuals who store water and the rationale of such storage allow a better understanding of the social dynamics that lead to water accumulation.